2020
DOI: 10.3102/0013189x20902121
|View full text |Cite
|
Sign up to set email alerts
|

Intrastate and Interstate Influences on the Introduction and Enactment of Campus Carry Legislation, 2004–2016

Abstract: Using a data set that captures the introduction and enactment of “campus carry” bills between 2004 and 2016, we examined how the state policy adoption and diffusion framework explains the policy process related to allowing concealed weapons on the campuses of U.S. colleges and universities. Panel data logistic regression analyses revealed that active shooter incidents, the percentage of Republicans in state government, citizen political ideology, and policy diffusion influence the introduction of campus carry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For example, because interpretation of state statutes and regulations is a subjective undertaking, others reviewing the same information we did might develop a different classification scheme than the one we developed. Furthermore, the results we obtained might be different had we approached how states regulate CCOC as an issue involving how they regulate higher education (see Johnson & Zhang, 2020) rather than how states regulate firearms. In addition, we are cognizant of the fact that because we are studying 50 states, the statistical analysis of the restrictiveness-by-institutional discretion framework we present may be limited empirically due to small cell sizes and the fact that some include zeroes.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 77%
See 3 more Smart Citations
“…For example, because interpretation of state statutes and regulations is a subjective undertaking, others reviewing the same information we did might develop a different classification scheme than the one we developed. Furthermore, the results we obtained might be different had we approached how states regulate CCOC as an issue involving how they regulate higher education (see Johnson & Zhang, 2020) rather than how states regulate firearms. In addition, we are cognizant of the fact that because we are studying 50 states, the statistical analysis of the restrictiveness-by-institutional discretion framework we present may be limited empirically due to small cell sizes and the fact that some include zeroes.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 77%
“…The political winds were thus blowing toward restrictive gun regulation. Sloan and Fisher (2018) and Johnson and Zhang (2020) also showed that, since the 2010 Tea Party "wave election" when Republicans not only retook control of the U.S. House of Representatives but also dozens of state legislatures and governorships, the political winds changed direction toward relaxing restrictive gun regulations. Evidence for this is seen in the fact that multiple states have considered at least one piece of legislation since 2010 designed either to ease or abolish completely existing restrictions on CCOC (Sloan and Fisher, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our data span from January 1999 to May 2020 for a total of 12,850 state‐months. We recognize the limitations of our data given that sales at gun shows and sales conducted by unlicensed dealers do not undergo background check; however, we adopted the approach of other scholars who have utilized firearm background checks as proxies for gun sales (Butz, Fix, and Mitchell, 2015; Johnson and Zhang, 2020).…”
Section: Methodsmentioning
confidence: 99%